The prediction of fatigue-related muscle adaptation in different workload during cycling rowing exercise - Hong, W. H.; Wang, H. J.; Chen, K. R.; Huang, M. H. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to identify the fatigue-related muscles during the different percentage of the maximal workload. Seven subjects were recruited and, firstly, performed the maximal workload test for 3 minutes. After 24 hours, the different workload tests (60%, 70% and 80% of the maximal workload) were used to reveal the fatigue-related muscle. The result showed that the biceps and triceps had the extreme contribution at the minor and greater workload. However, the neuromuscular fatigue threshold (NFT) is to predict the possibly fatigue muscle condition during the entire exercise. And the most contribution of the EMG expression didn`t stand for the greater value of the EMG number.